Positive reinforcement and the withdrawing behavior of the elderly - Orcajada, Vittorio Roy Nermal
The objective of the study is to determine how Behavior Modification using attention as reinforcement will change the withdrawing behavior of the elderly in Pavia and Jaro in Iloilo. Demographic variables of age, sex, educational attainment and geographical background are tested in this study to see if these are related to the progress in the behavior of the non-socializing elderly. The research method used is the Intra-subject Experimental technique, using the Reversal or ABAB Design. Results of the study yield information of diagnostic value. The author hopes that families with aging members will realize the needs of the elderly and be able to do something about them.